Religious Customs of Modern Michigan Algonquians - Kurath, Gertrude Prokosch (1955)
The draft of an unpublished book. Includes pictures and musical scores. Attempts, by detailed analysis and description of present-day customs in historical perspective to evaluate powwows, feasts, and camp meetings in Ottawa culture. Twelve chapters give brief history, biographies, and locations; describe festivals and dances in detail; analyze native songs (scores); describe a Chippewa Methodist camp meeting and hymns, with analysis of hymn texts and tunes. Also, presnnts Ottawa superstitions (bear walking, medicines, herbs), 42 Ottawa myths (see also #2642), material on natural-history usage. Attempts to reconstruct function of ritual, with historical references.